# Math Homework Help

We’ve answered 288,557 questions. We can answer yours, too.

### Showing All Questions Answered Popular Recommended Unanswered Editor's Choice in Math

• Math
We'll use the binomial raised to cube identity: (a+b)^3 = a^3 + b^3 + 3a*b*(a+b) In this case, a = x1 and b = x2 We'll replace a and b by x1 and x2 and we'll have: (x1+x2)^3 = x1^3 + x2^3 +...

Asked by pengui on via web

• Math
We have to solve: (cos x)^2 - (sin x)^2 + sin x = 0 (cos x)^2 - (sin x)^2 + sin x = 0 substitute (cos x)^2 = 1 - (sin x)^2 => 1 - (sin x)^2 - (sin x)^2 + sin x = 0 => 1 - 2*(sin x)^2 + sin x...

Asked by redsunshine on via web

1 educator answer.

• Math
Let the terms of a geometric progression be : a1, a2, a3, a4 Given that a3= 1 and the common difference is 1/2. ==> Then we know that: a3 = a1*r^2 1 = a1* (1/2)^2 1= a1/ 4 ==> a1= 4 ==>...

Asked by jojoogel on via web

2 educator answers.

• Math
Let us assume that the number is x. Then 3 times square x is 3x^2. And we will add 2 times fifth x ==> 3x^2 + 2x/5 = 3x^2 +(2/5)x ==> All divide by (x+7) ==> [(3x^2 + (2/5)x] / (x+7)...

Asked by genieee on via web

2 educator answers.

• Math
sqrt(x^2 + 3x -5) = x+ 2 First we will square both sides. ==> x^2 + 3x -5 = (x+2)^2 ==> x^2 + 3x -5 = x^2 + 4x +4 ==> 3x -5 = 4x+4 ==>. x = -9 Let us check. ==> sqrt( 81-27-5) =...

Asked by rogeryyo on via web

2 educator answers.

• Math
Let the first speed be S1 = 55 mph and the time is T1 = 24 min. The second speed is S2= 135 and the time is T2 = 135 min. We need to find the total distance . Let the total diostance be D = D1 +...

Asked by adreyano on via web

2 educator answers.

• Math
Given that : log a = 12 log b= 3 We need to find the value of the expression : log (a^2*b^3)^6 First we know that log a^b= b*log a. ==> log (a^2*b^3)^6 = 6*log (a^2*b^3) Now we know that log ab...

Asked by nadolla on via web

2 educator answers.

• Math
log3 (12n-1) - log3 (2x+7) = 2 First we will find the domain. ==> 12n-1 > 0 ==> n> 1/12 ==> 2n+7 > 0 ==> n > -7/2 Then The domain is n > 1/12 .............(1) Now we will...

Asked by zaidzoo on via web

2 educator answers.

• Math
81^2x = 27^(4x-1) First we will simplify by factoring the bases. ==> 81 = 3*3*3*3= 3^4 ==> 27 = 3*3*3 = 3^3 Now we will substitute. ==> 3^4^2x = 3^3^(4x-1) But we know that x^a^b= x^ab....

Asked by meterya on via web

2 educator answers.

• Math
f(x) = (3x^2-5) / x Let us simplify. ==> f(x) = 3x^2/x - 5/x ==> f(x) = 3x - 5/x Now we will integrate. ==> F(x) = Int (3x - 5/x) dx ==> F(x) = 3x^2/2 - 5*ln x ==> F(x) = (3/2)x^2 -...

Asked by neefo on via web

1 educator answer.

• Math
Given the curve f(x) = 2x^2 - 2 We need to find the area bounded between f(x) and x=1 and x= 2 Then we know that the area under the curve is the integral of f(x) between 1 and 2. ==> Then F(x)=...

Asked by roooze on via web

1 educator answer.

• Math
Given the polynomial equation: 3u^3 - u^2 -6u + 2 = 0 First we will factor the equation. We will factor u^2 from the first 2 terms. ==> u^2 ( 3u - 1) - 6u + 2 = 0 Now we will factor -2 from the...

Asked by alinnne on via web

2 educator answers.

• Math
We have to simplify 256^(log 4 (3)) 256^(log 4 (3)) => 4^4^(log(4) 3) => 4^(4*(log(4) 3)) use the property of logarithm: a*log b = log b^a => 4^(log(4) 3^4) => 4^(log(4) 81) the log of...

Asked by paulbarrow on via web

2 educator answers.

• Math
The average of the numbers with the incorrect entry is 56. The total of the 20 numbers is 56*20 = 1120. The incorrect value that is entered as 91 is actually 19. The excess that this error adds to...

Asked by justinenotes on via web

1 educator answer.

• Math
Let us review the rules for the geometric progression. Let a1, a2, a3, a4, a5, a6 are the first 6 terms is a G.P. Let r be the common difference. Then, we know that> a1= a1 a2= a1*r a3= a1*r^2...

Asked by hekmatzeft on via web

2 educator answers.

• Math
Let the price of the book be B and the price of the DVD be D. Given that 2 books and 3 DVDs costs 91 ==> 2B + 3D = 91 ..............(1) Also, given that the cost is 1 book and 2 DVDs is 52....

Asked by hatemaldeeb on via web

2 educator answers.

• Math
Given that 2x, 17, 3x-1 are terms is A.P Let us assume that the common difference is r. Then we know that: 17 = 2x + r ...........(1) Also we know that: 3x-1 = 17 + r => -18 = -3x +...

Asked by colinhartmann on via web

2 educator answers.

• Math
Given the curve y= x^2 - 5x + 3 and the curve y= 2x^2 - 3x + 4 We need to find the position of the intersection point. First we will determine the coordinates of the intersection points. ==>...

Asked by mytomcruise on via web

2 educator answers.

• Math
Given the circumference of the pool is 23 feet. Let us calculate the radius. ==> C = 2* r * pi ==> 23 = 2*r * pi ==> r= 23/2pi = 3.66 ft Now we need to determine the circumference of the...

Asked by ranironi on via web

2 educator answers.

• Math
Given the volume of the cylinder is 48 and the height is 7. We will use the volume of a cylinder formula to find the radius of the base. ==> V = r^2 * pi * h ==> 48 = r^2 * pi * 7 ==> r^2...

Asked by calraedwards on via web

2 educator answers.

• Math
Given the equation of the circle: x^2 + y^2 - 8x + 12y = 12 We need to rewrite the equation into the standard form in order to determine the radius. ==> (x-a)^2 + (y-b)^2 = r^2 Then we will need...

Asked by meganchamlee on via web

2 educator answers.

• Math
The inequality we have is 5-4l 2x-7l =< 13 5 - 4l 2x-7l =< 13 => 5 - 13 =< 4*|2x - 7| => -8 =< 4*|2x - 7| => -2 =< |2x - 7| But we know that |x| >=0 |2x - 7| >= 0 This...

Asked by delondavis on via web

1 educator answer.

• Math
y= log3 ( 5x^2-125) We need to find the domain. The domain is all x values such that the function y is defined. Since the function is a logarithm, then we know that the logarithm should be greater...

Asked by rightaid on via web

2 educator answers.

• Math
y= (2x-3) / (x^2 -1) We will use the quotient rule to find the derivative. Let y= u/ v such that" u= 2x-3 ==> u' = 2 v = x^2 -1 ==> v' = 2x Then we know that: y' = ( u'v- uv' ) / v^2 ==>...

Asked by reginakennedy on via web

2 educator answers.

• Math
An unbiased dice has 6 faces with a different number each of which has an equal probability of showing when the die is tossed. In the problem we have 3 unbiased dice. 1) First we need to find the...

Asked by lucky092569 on via web

1 educator answer.

• Math
The extreme value of f(x) = 3 - 4*sin x occurs at the value of x where f'(x) = 0 f'(x) = 0 - 4*cos x = 0 => cos x = 0 x = arc cos 0 = pi/2 and 3*pi/2 At the maximum point f''(x) is negative...

Asked by anonymous11 on via web

1 educator answer.

• Math
We have to find the properties of the roots of the given equation without solving it. We can determine if the roots are real or complex and whether they are the same or different. For the equation...

Asked by carolinesmiths on via web

1 educator answer.

• Math
The solution of x/y + y/x = 8 can be obtained by equating z = x/y This makes x/y + y/x = 8 => z + 1/z = 8 => z^2 – 8z + 1 = 0 z1 = 8/2 + sqrt (8^2 – 4) / 2 => 4 + sqrt 60 / 2 => 4 +...

Asked by xetabeta on via web

1 educator answer.

• Math
A quadratic equation does not have one root, instead it is referred to as the equation having 2 equal roots. A quadratic equation in the general form ax^2 + bx + c = 0 has the roots given by: x1 =...

Asked by xetaalpha2 on via web

1 educator answer.

• Math
The solution of the equation x^3 + 3x^2 + x + 3 = 0 can be found by finding the factors of the polynomial. x^3 + 3x^2 + x + 3 = 0 => x^2(x + 3) + 1(x + 3) = 0 => (x^2 + 1)(x + 3) = 0 x^2 + 1...

Asked by xetaalpha on via web

1 educator answer.

• Math
To verify sin(x + y) + sin(x - y) = 2 sin x cos y use the formula of the sin of the sum of two angles: sin (x + y) = sin x*cos y + cos x *sin y. sin(x + y) + sin(x - y) => sin x*cos y + cos...

Asked by anonymousse2 on via web

1 educator answer.

• Math
You'll have 4 answers for x in total. (x+10)=1 & (x+11)=1 & (x+12)=1 & (x+13)=1 X=-9 & x=-10 & x=-11 & x=-12 Done! :)

Asked by zanyx on via web

• Math
Given the quadratic equation : f(x) = 3x^2 + 5x + C We know that f(x) has two complex roots. Then the discriminant is negative. ==> (b^2 - 4ac < 0 a = 3 b= 5 c = C ==> 25 - 4*3*C <...

Asked by nano75 on via web

2 educator answers.

• Math
tanx*sinx* (cosx+1) + cosx = sin62 x+ sec x Let us start from the left side and prove the right side. We know that tanx = sinx/cosx ==> sinx/cosx * sinx ( cosx+ 1) + cosx ==> We will rewrite...

Asked by jude69 on via web

2 educator answers.

• Math
Given the equation of the circle is : x^2 + y62 - 2x + 8y = 13 We need to find the area. First we need to determine the radius. Then, we will rewrite the equation into the standard form. (x-a)^2 +...

Asked by ryanomar on via web

2 educator answers.

• Math
f(x)= 3x^2 - 4x + 5 we need to find the extreme value of f(x). First we will find the critical points. ==. f'(x) = 6x -4 = 0 ==> x = 4/6 = 2/3 Then the function f(x) has an extreme value at...

Asked by lalooo on via web

2 educator answers.

• Math
Given y= (2x-3) / (x+2) we need to find the intercepts of y. First we will determine the y-intercepts. Then x value is 0. ==> y= (0-3)/(0+2) = -3/2 Then the y-intercept is (0, -3/2) now we will...

Asked by kokibrazil on via web

2 educator answers.

• Math
Given that f(x) = sqrt( 5- l 3x-4l ) We need to find the domain of f(x). Since the function is a square root, then the domain is all x values such the function inside the square root is positive or...

Asked by totoo on via web

2 educator answers.

• Math
One of the roots of f(x) = ax^2 - 3x + 2 is 3. The function f(x) is equal to 0, when x is equal to any of its roots. The roots of f(x) are -b/2a + sqrt (b^2 - 4ac) / 2a => 3/2a + sqrt (9 - 8a) /...

Asked by feres on via web

1 educator answer.

• Math
There are two integers A and B. A is 3 less than twice B => A = 2*B - 3 The sum of the two is 12 => A + B = 12 => 2*B - 3 + B = 12 => 3B = 15 => B = 5 A = 12 - 5 = 7 The integers...

Asked by yasmin130 on via web

2 educator answers.

• Math
We have : log3(8x+3) = 1+ log3 (x^2) log3(8x+3) = 1+ log3 (x^2) => log3(8x+3) - log3 (x^2) = 1 use the property log a - log b = log (a/b) => log3 [(8x + 3)/(x^2)] = 1 => (8x + 3)/(x^2) =...

Asked by clara2 on via web

1 educator answer.

• Math
Given the derivative f'(x) = (x^3 - x)/4x^4 Let us simplify. ==> f'(x) = (x^3/4x^4) - x/4x^4 ==> f'(x) = (1/4x) - 1/4x^3 ==> f'(x) =(1/4)[ 1/x - x^-3) Now we will integrate. ==> f(x) =...

Asked by nadooosh on via web

2 educator answers.

• Math
To solve an equation like a*cos^2x+b*sinx=b, remember the basic identity (sin x)^2 + (cos x)^2 = 1 a*cos^2x+b*sinx=b => a*(1 - (sin x)^2) + b*sin x = b => a - a*(sin x)^2 + b*sin x = b =>...

Asked by pengui on via web

1 educator answer.

• Math
Let the three terms of the AP be a , b and c. Consecutive terms of an AP have a common difference b = a + d and c = b + d = a + 2d If you can determine a and d using the relations for the others in...

Asked by leslie29 on via web

1 educator answer.

• Math
Use the formula for the cosine of the sum of two angles cos (a + b) = cos a*cos b - sin a * sin b cos 2x = cos (x + x) => cos x*cos x - sin x * sin x => (cos x)^2 - (sin x)^2 This gives cos...

Asked by siteulove on via web

1 educator answer.

• Math
The request of the problem is vague since it is not clear what is needed, hence, supposing that you need to work with a fraction that has a complex number to dennominator, you need to perform first...

Asked by sensitiv on via web

1 educator answer.

• Math
The identity that has to be proved is: (tan A)^2/(1+ (tan A)^2) + (cot A)^2/(1+(cot A)^2) = (1- 2(sin A)^2 (cos A)^2)/(sin A)(cos A) Starting with the left hand side: (tan A)^2/(1+ (tan A)^2) +...

Asked by lbawa on via web

1 educator answer.

• Math
We need to find x if 5*6^x-2*3^2x-3*2^2x=0 5*6^x-2*3^2x-3*2^2x=0 divide all the terms by 2^2x => 5*(3/2)^x - 2*(3/2)^2x - 3 = 0 let (3/2)^x = y => 5y - 2y^2 - 3 = 0 => 2y^2 - 5y + 3 = 0...

Asked by else9393 on via web

1 educator answer.

• Math
We have to solve for x and y given that y=6/x and 2^(x+y)=32 substitute y = 6/x in 2^(x+y)=32 => 2^(x + 6/x) = 32 => 2^(x + 6/x) = 2^5 => x + 6/x = 5 => x^2 - 5x + 6 = 0 => x^2 - 3x...

Asked by denyss on via web

1 educator answer.

• Math
The equation to be solved is x=(x+6)^1/2 x=(x+6)^1/2 square both the sides => x^2 = x + 6 => x^2 - x - 6 = 0 => x^2 - 3x + 2x - 6 = 0 => x(x - 3) + 2(x - 3) = 0 => (x + 2)(x - 3) =...

Asked by zarvamea on via web

1 educator answer.

Showing 28051–28100 of 36,552